Stimulation of children with congenital Zika syndrome at home: challenges for the caregivers - Cora Coralina dos Santos Junqueira; Alane Barreto de Almeida Leôncio; Elenice Maria Cecchetti Vaz; Nathanielly Cristina Carvalho de Brito Santos; Neusa Collet; Altamira Pereira da Silva Reichert
ABSTRACT Objective: To identify the challenges faced by caregivers regarding the stimulation of the development of children with congenital Zika syndrome at home. Method: A qualitative study was carried out with ten caregivers of children with the syndrome and five health professionals who work in a specialized service of reference for children/adolescents with disabilities in a city in Pernambuco, Brazil. Data collection took place between November 2018 and March 2019 through a semi-structured interview, and the data were interpreted using thematic analysis. Results: The challenges faced by caregivers are permeated by fear, insecurity and lack of support for the realization of the stimulatory activities at home. Practitioners acknowledge the situation but emphasize the importance of continuing the stimulatory activities to preserve the capabilities of these children. Conclusions: It is necessary to sensitize health teams to support families regarding the challenges faced and provide full time care for the child with Zika syndrome in order to achieve maximum development.